Peningkatan Kemampuan Cuci Tangan Sesuai Standard WHO dalam Pencegahan Covid-19 Melalui Media Video pada Anak Pra Sekolah Lembaga Pendidikan (LP) Daarul Quran Fatchul Huda - Zahid Fikri; Muhammad Rosyidul ‘Ibad; Muhammad Ari Arfiyanto; Khikmatul Mu’jizah; Febriani Melania; Ismail Mahesba (Pelita Abdi Masyarakat, 2021)
Background : Prevention of Covid-19 recommended by the government is to wear masks and wash hands. Preschool children most often play games by using direct contact with their toys. Some even play outside and make direct contact with other friends. Children's ability to wash their hands needs to be improved because washing hands without proper procedures will have a negative impact on children. The purpose of this service is to increase the ability of pre-school children of the Daarul Quran Education Institute in doing proper hand washing according to WHO standards. This service is carried out at the Daarul Quran Educational Institution (LP) Bandungrejosari Sukun, Malang City. The implementation of learning is carried out using ppt and video media to further introduce and facilitate children's understanding of how to wash hands properly. Method : There are 30 children participating in the activity. The activity was carried out in the hall of the Daarul Quran LP while still complying with the Health protocol. Before the activity begins, the children are conditioned to pray and sing, then we first evaluate the children's knowledge and ability to wash their hands. Results : The initial results before being given the material, all children have not been able to wash their hands properly. The material is given for 30 minutes and there is also a video showing how to wash hands then the children are asked to practice with the help of the facilitator. The children were then tested again to practice hand washing. The result is an increase in children's ability to wash their hands properly. Conclusion : The ability of pre-school children to wash their hands using soap/hand sanitizer has increased when compared to before learning about hand washing.